Vascular complications after transcatheter transfemoral aortic valve implantation: Modified sheath-to-femoral artery ratio as a new predictor - Çakal, Sinem; Çakal, Beytullah; Karaca, Oğuz; Güler, Yeliz; Özcan, Özgür Ulaş; Güneş, Hacı Murat; Kızılırmak Yılmaz, Filiz; Yıldırım, Arzu; Boztosun, Bilal (NLM (Medline), 2022)
OBJECTIVE: Vascular complications (VCs) contribute to increased morbidity and mortality in patients who have undergone transcatheter aortic valve implantation (TAVI); however, studies on their incidence and predictors show conflicting results. In this study, we sought to assess the incidence, impact, and predictors of VCs in transfemoral (TF) TAVI and also investigated the predictive role of manufacturer's size charts and a new predictor modified sheath-to-femoral artery ratio. METHODS: A total of 223 patients undergoing TF-TAVI were categorized into 2 groups. The patients were divided as eligible and ineligible according to the manufacturer's guidelines (MG), and the same patient cohort was dichotomized into eligible and ineligible on the basis of sheath-to-femoral artery ratio (SFAR) value of less than or greater than or equal to modified SFAR (md-SFAR). VCs (defined according to the Valve Academic Research Consortium II criteria) were retrospectively compared. RESULTS: According to the manufacturer's size charts, 65 patients were unsuitable; however, 35 patients were ineligible for TF-TAVI per the md-SFAR criteria. Although VCs occurred in 42 (18.8%) patients, 17 (27.7%) of those patients were classified as ineligible according to MG, whereas 14 (41.2%) were classified as ineligible in the md-SFAR group. In a multiple logistic regression analysis that included md-SFAR, MG, SFAR ?1.05, peripheral artery disease, and minimum iliofemoral artery diameter, only md-SFAR was the independent predictor of VCs (odds ratio=3.71, 95% confidence interval=1.13-12.53, p=0.031). CONCLUSION: According to our results, md-SFAR might provide better patient selection to prevent VCs and improve outcomes in TF-TAVI procedures.
Keywords: Aortic Valve Stenosis; Aortic Valve Replacement; Complications; Heart Valve Disease; Transcatheter Aortic Valve Replacement